BUSINESS OPERATIONS: THEORY, PRACTICE, AND DEVELOPMENT PROSPECTS - Doniyor Umarov (Modern American Journals, 2025)
In the context of a rapidly changing global economic landscape, business operations have become the cornerstone of organizational resilience and competitiveness. This article offers a comprehensive study of business operations as a systemic management category, analyzing key trends in their organization and identifying strategic directions for optimization in the era of digitalization and globalization. The paper explores the theoretical foundations, current managerial practices, and innovative approaches that enhance the efficiency of an enterprise's operational model. Particular attention is given to the transformation of processes under the influence of Industry 4.0 technologies, supply chain management, digital twins, operational flexibility, and the resilience of business processes in times of crisis.
Keywords: business operations, operational management, efficiency, digitalization, supply chain, business processes, resilience, transformation, Industry 4.0, management